EIB Group Sustainability Report 2019 - European Investment Bank (European Investment Bank, 2020)
The EIB Group 2019 Sustainability Report provides an overview of the European Investment Bank Group's operations and impact as they relate to our objective to support smart, sustainable and inclusive growth in a challenging European and global context. The Sustainability report should be read in conjunction with the 2019 Sustainability Reporting Disclosures.